Forest Customs, Subsistence, and Need in the Municipal Ordinances of the Crown of Castile (15th-16th centuries) (Edad Media. Revista de Historia, 2026)
Forest practices played a central role in the subsistence of medieval communities. The intense and meticulous body of regulations promoted by local authorities from the 15th century onwards, aimed at governing and controlling peasant resource use had ambivalent consequences for the network of customary rights. While many forms of resource use were restricted, those deemed essential for meeting a wide range of needs were preserved. The study of late medieval municipal ordinances from various regions of the Crown of Castile reveals the existence of common trends, while also identifying distinctive features, according to the characteristics of each community organization.
Keywords: Forest Ordinances; Subsistence; Need; Castile; 15th-16th centuries